Taraxacum litardieri Soest - Štepánek, Jan; Kirschner, Jan (Zenodo, 2013)
Taraxacum litardieri Soest in Acta Bot. Neerl. 6: 416. 1957 (Fig. 1B). Lectotypus (designated by JEANMONOD, 2010): CORSE: “ Punta Artica, éboulis morainique”, 2250 m. env., 2.VIII. 1908, R. de Litardière s.n. (G [G00000879], specimen designated by “*”, n° det. 23231; iso-: L [953133126], cf. JEANMONOD, 2010). Description. – Plants relatively small, (4-)7-14(-18) cm tall, sometimes with several root heads; plant base scarcely covered with dry blackish remnants of old petioles, brownish hairy among petiole bases. Leaves with a relatively simple lobation, usually 5-12 cm long, 1.5-2.5 cm wide, mid-green to [??] paler green, not spotted; leaf blade spatulate to broadly spatulate in outline, ± undivided or usually pinnatilobed or pinnatipartite, rarely pinnatisect, ± obtuse to rounded at the apex, the most common leaf shape with distal 1/2-1/5 undivided and ± entire, proximal part remotely shallowly dentate or lobed, sometimes leaf blade with 2-3(4) pairs of more distinct short, broad, subacute lobes, distal margin usually sigmoid, proximal margin short, ± concave; midrib probably pale; petioles narrow to narrowly winged, usually 1-5 cm long, pale. Scapes usually 3-6, thin, overtopping leaves, glabrous, probably pale green. Capitulum small, 1-1.5 cm in diam., most probably deep yellow to orange-yellow. Involucre ± rounded at base, probably not pruinose. Outer involucralbracts (11-) 13-20, ovatelanceolate, lanceolate to linear-lanceolate, relatively short (as long as 2/5-1/2 of the inner, (3.5-) 4-6 mm long, (1-)2.0-2.5 (-4) mm wide, the outermost one usually ± linear, ca. 1 mm wide, irregularly loosely appressed to erect, blackish, without border or with almost invisible very narrow paler border, not ciliate or very minutely ciliate, flat, with ± paler tip; inner involucral bracts ca. 11 mm long, of ± equal width, sometimes laterally fused, slightly callose below apex. All ligules ± cylindrical, with fused margins, outer ligules striped grey-blackish outside (the whole abaxial side of ligules dark), apical teeth black, inner ligules with apical teeth greyish. Stigmas rarely exserted (usually hidden in the cylindrical ligule), discoloured (greyish), sometimes dark greyish (never black), pale pilose outside. Pollen not developed (or with sparse rudimentary pollen in the angles of the anther tube). Achenes light grey-brownish or pale straw-brown, (3.7-) 4.1-4.5 mm long, 0.8-0.9 mm wide, achene body with very short spinules and minute transversal crests (minute squamules) in the upper 1/5, otherwise ± smooth, gradually narrowing into conical (or conical at base and subcylindrical distally), relatively broad cone 0.5-0.8 mm long; rostrum (3.5-) 4-7.5 mm, pappus yellowish dirty white, 5-6 mm long. Agamosperm. Distribution. – Endemic to Corsica. Taxonomical position. – Taraxacum litardieri was initially classified as a member of sect. Pachera Soest, a group requiring a revision together with the other groups close to or belonging to sect. Arctica . However, T. litardieri is very close to the Alpine T. saasense Soest (with differences mainly in floret and achene characters) and, in all likelihood, belongs to sect. Alpina , at least according to the achene and outer bract characters. The single continental record of T. litardieri (Alpes Maritimes, cf. SOEST, 1957) is considered doubtful (we have seen an ample Taraxacum material from the Alpes Maritimes but no plant matched the peculiar characters of T. litardieri the closest neighbour of the latter is T. saasense ). We therefore consider T. litardieri as strictly endemic to Corsica. Specimens studied. – CORSE: Massif du Cinto, Monte Von Cube, versant N, pelouse fraîche (Gnaphalieto-Sibbaldietum) , 2080 m, sur rhyolites, 17.VIII.1971, J. Gamisans 913 (G [G00000779], n° det. 23243); Massif du Cinto, cirque de Trimbolacciu, éboulis, 1880 m., substr. siliceux, 6.VIII.1970, J. Gamisans 2527 (G [G00000783], n° det. 23247); Niolu Pinerole, versant N, couloir herbeux, pelouse subalpine, 1900 m, 12.VII.1977, J. Gamisans 6851 (G [G00000812], n° det. 23237); Punta Artica, éboulis morainique, 2250 m env., 2.VIII.1908, R. de Litardière (syntype, G [G00000879], n° det. 23231); Secteur Rotondu, Lac d’Oriente, massif du Rotondo, près du Lac d’Oriente [42°14’N 9°04’E], silice, 2050-2100 m, 28.VII.1974, R. Deschâtres (G [G00178578], n° det. 23253); Secteur Rotondu, Lac d’Oriente, massif du Rotondo, près du Lac d’Oriente [42°14’N 9°04’E], silice, 2100 m, 28.VII.1974, R. Deschâtres (G [G00178577], n° det. 23251); Monte Rotondo, éboulis au-dessus du lac d’Oriente, vers 2200 m, 13.VIII.1908, R. de Litardière (syntype, G [G00000870], n° det. 23230); Massif du Rotondo, versant N du Capo a i Sorbi, 2100 m, pelouse, substr. siliceux, 29.VII.1969, J. Gamisans 2522 (G [G00000787], n° det. 23241); Monte Rotondo, versant du lac de Pozzolo, rocailles, 2500 m env., 25.VIII.1919, R. de Litardière (syntype, G [G00000869], n° det. 23229); Massif du Rotondo, pelouse en bordure du lac de Bataniello, 2400 m, substr. siliceux, 29.VII.1966, J. Gamisans 2507 (G [G00000780], n° det. 23232); Monte Rotondo, versant N, 2250 m, pelouse fraîche, 8.VIII.1968, J. Gamisans 2519 (G [G00000786], n° det. 23248); Massif du Rotondo: au-dessus du lac Cavaccioli, pelouses à Sagina pilifera , 1850 m env., 1.VIII.1932, R. de Litardière (syntype, G [G00000887], n° det. 23228); Massif du Rotondo, lac de Cavaccioli, pelouse méso-hygrophile en bordure du lac, 2000 m, substr. siliceux, 3.VIII.1967, J. Gamisans 2509 (G [G00000782], n° det. 23246); Monte Rotondo: au-dessus du lac Scapuccioli, rochers, silice, 2100-2500 m, 6.VIII.1906, E. Burnat, J. Briquet, A. Saint-Yves, F. Cavillier & E. Abrezol (G-BU [G00001419], n° det. 23258); Massif du Rotondo, pentes rocailleuses entre les lacs de Cavaccioli et Scappaccioli, graviers humides, 2270 m, substr. siliceux, 3.VIII.1967, J. Gamisans 2511 (G [G00000788], n° det. 23235); Massif du Rotondo, couloir rocailleux dominant vers le SE, le lac de Scappaccioli, 2420 m, substr. siliceux, 3.VIII.1967, J. Gamisans 2510 (G [G00000781], n° det. 23234); Monte Rotondo, vers. S, Geo-Phleetum , 2400 m, 21.VII.1982, J. Gamisans 10124 (G [G00000810], n° det. 23255); Monte d’Oro, versant Est, rochers, silice, 2100 m, 9.VIII.1906, E. Burnat, J. Briquet, A. Saint-Yves, F. Cavillier & E. Abrezol (G-BU [G00001420], n° det. 23263); Monte d’Oro, versant Est, rochers, silice, 2100 m, 9.VIII.1906, E.Burnat, J. Briquet, A. Saint-Yves, F. Cavillier & E. Abrezol (G-BU [G00000829], n° det. 23261); Monte d’Oro, plateforme verte, silice, vers 2000 m, 17.VII. 1961, R. Deschâtres (G [G00178826], n° det. 23238); Monte d’Oro, parmi les blocs rocheux près de la Plateforme verte, silice, vers 2200 m, 13.VIII.1967, R. Deschâtres (G [G00178585], n° det. 23250); Env. de Bocognano: Punta dell’ Oriente, versant N.-E., cheminées des rochers, silice, 2000 m, 13.VII.1913, J. Briquet & E. Wilczeck (G [G00000835], n° det. 23266); Massif du Renoso, Monte Renoso, versant NE, pelouse fraîche ( Geo-Phleetum ), 2100 m, granite, 29.VII.1974, J. Gamisans 3634 (G [G00000778], n° det. 23244); Secteur Renosu, Lac de Bastani, près des rives du Lac Bastani, Monte Renoso [42°04’N 9°08’E], silice, 2080-2100 m, 19.VII.1975, R.Deschâtres (G [G00178586], n° det. 23249); Secteur Renosu, Monte Renoso [42°04’N 9°08’E], silice, 1900-2100 m, 8.VIII.1974, R. Deschâtres (G [G00178580], n° det. 23252); Massif du Renoso, versant N de la crête entre le monte Torto et le col de Rina, éboulis, 2150 m, substr. granitique, 24.VII.1968, J. Gamisans 2517 (G [G00000808], n° det. 23233); Mont Incudine, versant N, lisière des aulnaies, silice, 1900 m, 25.VII.1910, J. Briquet, A. Saint-Yves & Fr. Cavillier (G-BU [G00101161], n° det. 23268); Signal près du Monte Incudine, versant NNE, couloir herbeux frais, 2000 m, substr. siliceux, 18.VII.1971, J. Gamisans 632 (G [G00000807], n° det. 23254); Signal près du Monte Incudine, versant NNE, couloir herbeux frais, 2000 m, substr. siliceux, 14.VII.1968, J. Gamisans 2514bis (G [G00000811], n° det. 23256); Signal près du Monte Incudine, versant NNE, couloir herbeux frais, 2000 m, substr. siliceux, 18.VII.1971, J. Gamisans 632 (G [G00000784], n° det. 23239); Signal près du Monte Incudine, versant NNE, couloir herbeux frais, 2000 m, substr. siliceux, 16.VII.1967, J. Gamisans 2513 (G [G00000785], n° det. 23236). Uncertain identification. – CORSE: Massif du Cinto, “Cirque de la Solitude”, rocailles fraîches, 2050 m, substr. rhyolites, 17.VIII.1971, J. Gamisans 933 (G [G00000795], n° det. 23274); Monte Renoso, versant NE, pelouse fraîche ( Geo-Phleetum ), 2100 m, substr. granitique, 29.VII.1974, J. Gamisans 3644 (G [G00000777], n° det. 23245); Massif du Renoso, Punta dell’Oriente, près du sommet, rocailles, 2100 m, substr. granitiques, 25.VII.1966, J. Gamisans 2506 (G [G00000789], n° det. 23242); Signal près du Monte Incudine, versant NNE, couloir herbeux frais, 2000 m, substr. siliceux, 14.VII.1968, J. Gamisans 2514 (G [G00000776], n° det. 23240). : Published as part of Štepánek, Jan & Kirschner, Jan, 2013, A revision of mountain species of the genus Taraxacum F. H. Wigg. (Compositae) in Corsica, pp. 29-39 in Candollea 68 (1) on pages 32-33, DOI: 10.15553/c2013v681a2, http://zenodo.org/record/6028817 : {"references": ["SOEST, J. L. VAN (1957). Contribution a l'etude des Taraxacum de Corse. Acta Bot. Neerl. 6: 407 - 419.", "JEANMONOD, D. (2010). Typification des taxons corses de l'herbier de Litardiere. Candollea 65: 23 - 44."]}